The singing rooster a Manobo chief emphasizes the Manobo work ethic - Wrigglesworth, Hazel J.; Zacharius, Tigar; Linguistic Society of the Philippines (Manila Linguistic Society of the Philippines, 2009)
A selection of six narrative, as told by four Ilianen Manobo reconteurs, along with a description of the dynamic array of rhetorical devices for enabling the Manobo storyteller to become a master of dramatic entertainment--P. [4] of cover.
Story about Ukap -- The Monkey and the turtle -- Kereuu and Tingengew -- Gaun -- Kavus -- Tingengew.
English and Ilianen Manobo.
English and Ilianen Manobo.
Keywords: Oral tradition -- Philippines -- North Cotabato; Manobos (Philippine people) -- Folklore; Work ethic -- Philippines; Storytelling -- Philippines -- North Cotabato